PEMAKNAAN JEMAAT TERHADAP TINDAKAN MEMBERI SEBAGAI WUJUD PERKEMBANGAN IMAN DI GKJ SELOKATON KARANGANYAR - Santoso, Samuel Ariesta Putra Perdana; Juntak, Justin Niaga Siman (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to understand the meaning of the act of giving offerings among the congregation of the Javanese Christian Church (GKJ) Selokaton Karanganyar in relation to the development of faith. The background of this study is based on the importance of understanding the spiritual motivation behind the practice of giving offerings, which is often viewed as merely an administrative obligation of the church. The focus of the study is directed at how the congregation's perceptions and experiences in giving offerings reflect the growth of their faith. This study uses a descriptive qualitative approach with data collection through in-depth interviews with five active congregation informants. The research steps include identifying informants, conducting interviews, and thematic analysis of the data obtained. The results of the study show that giving offerings is interpreted as a form of obedience to God, an expression of gratitude, and responsibility as a member of the body of Christ. The more the congregation's faith develops, the more sincere and conscious the act of giving is. The main conclusion of this study emphasizes that the development of faith plays an important role in shaping the motivation and quality of giving offerings, so that the church needs to foster the faith of the congregation so that the act of giving becomes an integral part of worship and spiritual relationship with God. ABSTRAKPenelitian ini bertujuan untuk memahami makna tindakan memberi persembahan di kalangan jemaat Gereja Kristen Jawa (GKJ) Selokaton Karanganyar dalam kaitannya dengan perkembangan iman. Latar belakang penelitian ini didasari oleh pentingnya memahami motivasi spiritual di balik praktik memberi persembahan, yang sering kali dipandang sekadar sebagai kewajiban administratif gereja. Fokus penelitian diarahkan pada bagaimana persepsi dan pengalaman jemaat dalam memberi persembahan mencerminkan pertumbuhan iman mereka. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan pengumpulan data melalui wawancara mendalam terhadap lima informan jemaat yang aktif. Langkah penelitian meliputi identifikasi informan, pelaksanaan wawancara, dan analisis tematik terhadap data yang diperoleh. Hasil penelitian menunjukkan bahwa memberi persembahan dimaknai sebagai bentuk ketaatan kepada Tuhan, ungkapan syukur, dan tanggung jawab sebagai anggota tubuh Kristus. Semakin berkembang iman jemaat, semakin tulus dan sadar pula tindakan memberi yang dilakukan. Simpulan utama penelitian ini menegaskan bahwa perkembangan iman berperan penting dalam membentuk motivasi dan kualitas pemberian persembahan, sehingga gereja perlu membina iman jemaat agar tindakan memberi menjadi bagian integral dari ibadah dan relasi spiritual dengan Allah.